Physical principle and advances in plasmon-enhanced upconversion luminescence. (June 2019) - Zong, Huan; Mu, Xijiao; Sun, Mengtao
Abstract: In this review, we introduced the principle and advances in plasmon-enhanced upconversion luminescence. Firstly, we focus on the physical mechanism and principle of plasmon-enhanced upconversion luminescence, based on quantum electrodynamics. Secondly, we introduce in detail the advances in plasmon-enhanced upconversion luminescence, including plasmon-enhanced UC luminescence by metal/films, core-shell upconversion nanocrystals, plasmonic arrays/cavity and metal tip. Our review can not only promote deeper understanding quantum electrodynamics based plasmon-enhanced upconversion luminescence, but also can enlighten the potential applications of plasmon-enhanced upconversion luminescence.